On exit : interdisciplinary perspectives on the right of exit in liberal multicultural societies - Borchers, Dagmar, 1965-; Vitikainen, Annamari (De Gruyter, 2012)
On Exit provides fresh, new perspectiveson the debates on the rights of individuals against their own cultural or religious groups. It brings together scholars from different disciplines to discuss some of thekey questions concerning the relations of cultural and religious groups, group members, citizens, and the state within Western liberal democracies. The volume revisits some of the theoretical controversiesrevolving aroundthe right of exit, and provides insights into the more practical problems of cultural accommodation.